Experimental evaluation of IEEE 802.15.4/ZigBee for multi-patient ECG monitoring - Fernández-López, Helena (2011)
IEEE 802.15.4/ZigBee wireless sensor networks (WSNs) are a promising alternative to cabled systems for patient monitoring in hospitals. Some areas where monitoring systems based on WSNs can be successfuly used are ambulatory, waiting and triage rooms, post-op, and emergency rooms. The low power and small size ZigBee devices have the ability to form self-configuring networks that can extend themselves through a hospital wing or floor. Using spatially distributed networks, it is possible to cover an extended area and serve several patients. However, the low data rate protocols provided by IEEE 802.15.4 poses several challenges, mainly because its protocols were primarily designed to operate in low traffic load scenarios but some vital signs sensors generate a large volume of data. This work presents an experimental evaluation of the performance of multi-hop ZigBee networks comprised of several nodes that carry the traffic of wearable electrocardiogram (ECG) sensors. The results indicate that star networks can relay 100% of the traffic generated by at least 12 ECG nodes. In tree topologies, the increase of the network traffic load reduces the performance but even these networks can reliably relay the traffic of a considerable number of ECG nodes.